Optimal Incentives for Patent Challenges in the Pharmaceutical Industry - Enrico Böhme; Jonas Severin Frank; Wolfgang Kerber (Review of Industrial Organization, 2021)
In this paper, we show that a provision in antitrust law to allow patent settlements with a later market entry of generics than the date that is expected under patent litigation can increase consumer welfare. We introduce a policy parameter for determining the optimal additional period for collusion that would incentivize the challenging of weak patents and maximize consumer welfare. While in principle, later market entry leads to higher profits and lower consumer welfare, this can be more than compensated for if more patents are challenged as a result.
Keywords: 330; Antitrust; Collusion; Patent challenges; Patent settlements; Pharma